Using of Multivariate Hotelling T2 Quality Control Charts in Bazyan Cement Factory - Delshad Shaker Ismael Botani; Mardin Samir Ali; Sherzad Kareem Othman (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Cement is representing the major element of concrete ingredient and most of Kurdish houses and buildings depending on concrete structure. Cement has physical and chemical characteristics that rely on them to attain good quality. Using quality control charts to know that the process is under control or not could be apply on cement factories in Kurdistan Regional Government (KRG). The objective of this paper is to use univariate and multivariate Quality Control Charts (QCC) to monitor the cement production in Bazyan factory. The data analyses were done through Statgraphics v.16 mainly for 4 cement characteristics (1 physical and 3 chemical) with 100 observations for each characteristic. The data was divided into 25 subgroups and then X-bar charts founded for the variables and compared them with the results of multivariate QCC using Hotelling T2. It was discovered that the process is not under control due to 2 chemical characteristics (Al2O3 and SO3). It is recommended to use the suggested multivariate chart by responsible authority especially the directorates concerned with monitoring of cement factories